CLCN5 5'UTR isoforms in human kidneys: differential expression analysis between controls and patients with glomerulonephritis. (3rd February 2020) - Ceol, Monica; Gianesello, Lisa; Tosetto, Enrica; Priante, Giovanna; Del Prete, Dorella; Anglani, Franca
Abstract : ClC-5, the electrogenic chloride/proton exchanger strongly expressed in renal proximal tubules, belongs to the endocytic macromolecular complex responsible for albumin and low-molecular-weight protein uptake. ClC-5 was found to be overexpressed in glomeruli of glomerulonephritis and in cultured human podocytes under albumin overload. The transcriptional regulation of human ClC-5 is not fully understood. Three functional promoters of various strengths and 11 different 5' untranslated region (5'UTR) isoforms of CLCN5 messenger RNA (mRNA) were detected in the human kidney (variants 1–11). The aim of this study was to investigate the expression pattern of CLCN 5 5'UTR variants and the CLCN5 common translated region in glomerulonephritis. The 5'UTR ends and the translated region of CLCN5 mRNA were analyzed using quantitative relative real-time PCR or quantitative comparative endpoint PCR with GAPDH as housekeeping gene in 8 normal kidneys and 12 renal biopsies from patients with glomerulonephritis. The expression profile for all variants in normal and glomerulonephritis biopsies was similar, and variant 3 and alternative variant 4 were the most abundantly expressed in both sets. In glomerulonephritis biopsies, isoforms under the control of a weak promoter (variants 4, 6 and 7) showed an increased expression leading to an increase in the CLCN5 translated region, underscoring their importance in kidney pathophysiology. Since weak promoters can be turned on by different stimuli, these data support the hypothesis that proteinuria could be one of the stimuli capable of starting a signaling pathway that induces an increase in CLCN5 transcription.